Promising practices to support family involvement in schools - Hiatt-Michael, Diana B. (Emerald Publishing Limited : Information Age Publishing, 2010)
Promising Practices to Support Family Involvement in Schools is a must-have volume for every contemporary educator. This monograph provides a broad array of exciting research-supported practices to reform schools for the benefit of students, teachers, administrators, families and their communities. These practices will lead to higher student academic and school satisfaction outcomes. Experts in the field prepared this highly readable volume for teachers, school administrators, educational researchers, policymakers, and university faculty. The authors share their decades of educational research, wise insights and practical experiences with hopes to better life for individual families, educators, and society. This book belongs on every educator's desk!